To solve the system of equations using the elimination method, let's start with the original equations:
- \( \frac{1}{3}x + y = 3 \)
- \( 2y = -\frac{2}{3}x + 10 \)
First, it's best to eliminate the fractions in these equations for easier manipulation. We can do this by multiplying each equation by a common factor.
Step 1: Remove the Fractions
For the first equation, multiply the whole equation by 3:
\[
3\left(\frac{1}{3}x + y\right) = 3 \cdot 3 \
x + 3y = 9 \quad \text{(Equation 1')}
\]
For the second equation, multiply the whole equation by 3 to eliminate the fraction:
\[
3\left(2y\right) = 3\left(-\frac{2}{3}x + 10\right) \
6y = -2x + 30 \
2x + 6y = 30 \quad \text{(Equation 2')}
\]
Step 2: The New System
Now we have the following system of equations:
- \( x + 3y = 9 \) (Equation 1')
- \( 2x + 6y = 30 \) (Equation 2')
Step 3: Elimination
Notice that Equation 2' can be simplified by dividing by 2:
\[
x + 3y = 15 \quad \text{(Equation 2'')}
\]
Now the new system is:
- \( x + 3y = 9 \)
- \( x + 3y = 15 \)
Step 4: Subtract the Equations
Next, we'll subtract Equation 1' from Equation 2'':
\[
(x + 3y) - (x + 3y) = 15 - 9 \
0 = 6
\]
This leads us to a contradiction (0 cannot equal 6). This means that the two equations represent parallel lines, which implies that they do not intersect.
Conclusion
Since there is no solution to the system of equations, we conclude that the system is inconsistent. The two lines represented by the equations are parallel and thus do not meet at any point in the coordinate plane. Therefore, there are no values of \( x \) and \( y \) that satisfy both equations simultaneously.